Analisis Rekrutmen Dalam Meningkatkan Kinerja Karyawan Mie Muslim Sumenep - Sa'ie, Moh.; Farok, Umar; Mafluhah; Wafi, Abd; Sultoni, Mohammad Hamim (Mabny: Journal of Sharia Management and Business, 2024)
Recruitment is the process of selecting the right individuals for certain positions within the company so that these individuals can do a good job and remain in the company for a long time. This research was conducted at Mie Muslim Sumenep, located in Jalan Letnan Merta, Sumenep City District. This study aims to analyze recruitment in improving the performance of Sumenep Muslim Noodle employees. This type of research uses descriptive qualitative. Data collection methods in this study consist of observation, interviews and documentation. The results showed that Mie Muslim Sumenep uses external sources with the referral method or employee recommendations and advertising in the implementation of recruitment because the performance of employees obtained from the referral method is better than the advertising method. Through the referral program, the owner of Mie Muslim Sumenep can better recognize employee actions and appreciate the efforts made. That way a good quality relationship will be created between employees and companies that can improve employee performance